Opportunities for success: perceptions of intensive supervision probation with services - Pleggenkuhle, Breanne (Journal of crime and justice, 2025)
Probation remains at the forefront in relation to criminal justice supervision strategies. Many variations of probation exist, including intensive forms of community supervision for individuals classified as higher risk. Debate remains ongoing as to the efficacy of such forms of supervision, but most scholars agree that paired with services and treatment, community supervision at a variety of levels holds promise though the degree to which those under supervision agree remains in question. The current study examines the perceptions of those under an intensive supervision and services program, highlighting the experiences of 90 individuals participating in an intensive supervision with services program. Utilizing flexible coding and thematic analysis of responses to open-ended questions regarding the nature of supervision experiences, the results lend insight into what is perceived to be working – or challenging – regarding participation. Most participants indicated the structure, clarity, and service access promoted overall well-being and potential desistance, though structural challenges and time demands could limit the longer-term effectiveness of this type of supervision. These findings suggest probation programs may incorporate specific components to better supervision outcomes.